“Our Hujra is deserted”: Conflict, Violence, culture and ethnic identity among the Pukhtuns of Swat, Pakistan - Azim, Syed Wasif; Baloch , Zarmina; Saleem , Asif (International Journal of Psychosocial Rehabilitation, 2020)
Theoretically, while critically extending constructivist position, this study proposes that conflict and violence, like other factors, impacts cultures and have repercussions for ethnic identity. Conflict and violence may lead to least or no practice of culture, a performing marker of ethnic identity, however, ethnic identity does not ‘soften’ or ‘harden’ nor is lost. In fact, the impacts for ethnic identity and culture are multiple and complex. Focusing on Hujra and Melmastya, Pukhtun society 's essential and core institutions and codes, and ethnic identity symbols, we argue that the armed struggle in Swat, rebels, and the Pakistani state abused and transformed Pukhtun culture, an icon of ethnic identity and character in Pukhtun. We contend that the complete social and cultural code of Pukhtunwali and its essential elements, such as Hujra, Melmastya, was not followed in Swat Pukhtuns. Compared to the insurgents' and military impacts, our argument is that while they all had separate tactics, they all made a major contribution to Melmastya's "desertion of Hujra" and decline. In this situation, Swat's consequent interpretation is that 'the hujra community is now extinct in its ideal context.' Yet in Swat, Pukhtuns perceives these results as socially detrimental to the society and ethnic heritage of Pukhtun. This has consequences for Pukhtun's culture and ethnic origin. Methodologically, the thesis is based on a fieldwork, conducted in various parts of Swat between November 2016 and May 2017 for PHD research.